Japan's modern theatre : a century of change and continuity - Powell, Brian, 1939- (Japan Library, 2002)
This book endeavours to unravel the complicated skeins of Japanese theatre in the modern period and offers an appreciation of the richness of choice of presentational and representational theatre forms. Since the end of world War II there has been continuing but different conflict between the major theatrical genres. Kabuki continues to defend its ground successfully, but the 'new drama' (shingeki) became firmly established in its own right in the 1960s. It was a vigorous and exuberant 'underground' theatre which exploited anything and everything in the Japanese and western theatre traditio.